EVALUATION PLANNING LIGHTS SIGNALIZED AND DESIGN WEDENING PRINCE STREET SURYANATA - ROAD KADRIE OENING IN SAMARINDA - HADIJAH, SITI (KURVA S JURNAL MAHASISWA, 2014)
SITI Hadijah , NPM : 10.11.1001.7311.006 , " Evaluation Planning And Design Lamp signalized P.Suryanata Road Widening - Road Kadrie Oening in Samarinda " , Supervisor I : Ir . John Nono Sudarsono , MT ,Supervisor II And : Sahrullah , ST , MT         Traffic Planning activities include inventory and Evaluation Service Levels . BETWEEN inventory intent lying FOR knowing Service Level on any roads and interchanges . Purpose Service Level hearts husband CONDITIONS It is the ability of roads and interchanges FOR accommodate differences noticed Traffic WITH SPEED And Safety factor . Desired Service Level setting . In determining the level of service is desirable done for example by paying attention to: General Plan Transportation road network ; Role , capacity , and the characteristics of the road , road class , the characteristics of Traffic , Environmental Aspects , Social Aspects And ekonomi.penetapan solving traffic problems , preparation and Program Implementation Plan realization.